Evaluation of properties of magnesian lime mortar - PAVIA, SARA (WIT Press, 2005)
Due to their nature and function, historic lime mortars weather and often need to be replaced. Petrographic analysis of original mortars from Ardamullivan Castle evidenced that they were fabricated with a dolomitic limestone. Within, Ardamullivan Castle?s conservation programme it was considered to replicate the original mortars to undertake conservation works to the Castle. However, documentary research revealed that there is a lack of agreement on the properties of magnesian lime as well as a lack of experimental work in the subject. Therefore, it was deemed necessary to evaluate the properties of magnesian lime prior to its use. To this aim, dolomite was calcinated in a limekiln and the lime obtained slaked for a year. Magnesian lime mortars were then fabricated and tested in the laboratory. Porosity, densities, compressive strength, capillary suction and absorption were evaluated. The lower values of capillary raise, porosity and absorption obtained for the magnesian lime mortars when compared to those of feebly hydraulic limes suggest that magnesian lime binders would perform superiorly in areas subject to the presence of moisture. In compression, the feebly-hydraulic mix is four times stronger than the mg-lime mortar. The mg-lime mortar outperforms the feebly-hydraulic lime mix in all tests except for compressive strength. However, the compressive strength of the mg-lime mix is enough to withstand the stresses and strains typically induced when confined within conventional masonry. The results of this investigation suggest that, provided the lime has been adequately calcinated and slaked, mg-lime mortar can perform well as a building material.
Structural Studies, Repair and Maintenance of Heritage Architecture IX.
PUBLISHED
Keywords: Magnesian lime; lime mortar; hydraulicity; NHL2; capillary suction; water absorption; porosity; densities; permeability; compresive strength